Punctuated shutdown of Atlantic meridional overturning circulation during Greenland Stadial 1 - Hogg, Alan G.; Southon, John; Turney, Chris; Palmer, Jonathan; Ramsey, Christopher Bronk; Fenwick, Pavla; Boswijk, Gretel; Friedrich, Michael; Helle, Gerhard; Hughen, Konrad; Jones, Richard; Kromer, Bernd; et al. (Scientific reports, 2016)
The Greenland Stadial 1 (GS-1; ~12.9 to 11.65 kyr cal BP) was a period of North Atlantic cooling, thought to have been initiated by North America fresh water runoff that caused a sustained reduction of North Atlantic Meridional Overturning Circulation (AMOC), resulting in an antiphase temperature response between the hemispheres (the ‘bipolar seesaw’). Here we exploit sub-fossil New Zealand kauri trees to report the first securely dated, decadally-resolved atmospheric radiocarbon (14C) record spanning GS-1. By precisely aligning Southern and Northern Hemisphere tree-ring 14C records with marine 14C sequences we document two relatively short periods of AMOC collapse during the stadial, at ~12,920-12,640 cal BP and 12,050-11,900 cal BP. In addition, our data show that the interhemispheric atmospheric 14C offset was close to zero prior to GS-1, before reaching ‘near-modern’ values at ~12,660 cal BP, consistent with synchronous recovery of overturning in both hemispheres and increased Southern Ocean ventilation. Hence, sustained North Atlantic cooling across GS-1 was not driven by a prolonged AMOC reduction but probably due to an equatorward migration of the Polar Front, reducing the advection of southwesterly air masses to high latitudes. Our findings suggest opposing hemispheric temperature trends were driven by atmospheric teleconnections, rather than AMOC changes.
Gesehen am 19.05.2020